Deciphering the Pharmacological Mechanisms of Ma Xing Shi Gan Decoction against COVID-19 through Integrating Network Pharmacology and Experimental Exploration - Li, Qianqian; Bai, Chen; Yang, Ruocong; Xing, Weiying; Pang, Xiaohan; Wu, Siying; Liu, Shaoyang; Chen, Jianxin; Liu, Tiegang; Gu, Xiaohong (Frontiers in Pharmacology, 2020)
The outbreak of new infectious pneumonia caused by SARS-CoV-2 has posed a significant threat to public health, but specific medicines and vaccines are still being developed. TCM has thousands of years of experience in strengthening the resistance to epidemic diseases, with distinct insights and experience in prevention and treatment. In particular, TCM have made remarkable contribution to the prevention, treatment and rehabilitation of influenza and viral pneumonia. The aim of this study is to reveal the efficacy and pharmacological mechanism of MXSG against COVID-19. We used liquid chromatography-mass spectrometry (LC-MS) to analyze the chemical components in MXSG and identify a total of 97 components from MXSG. Then, the Intervention pathway of MXSG based on these components was analyzed through network pharmacology, and it was found that some of MXSG component targets were enriched in the pathway of virus infection. At the same time, through literature research, it was preliminarily determined that MXSG, as a basic prescription for treating COVID-19, has the efficacy of antiviral, improving clinical symptoms, regulating immune inflammation and inhibiting lung injury. The regulatory mechanisms associated with its treatment of COVID-19 were proposed. MXSG might directly inhibit the adsorption and replication of SRAS-CoV-2 by interfering the interaction between PI3K/AKT and virus invasion and replication. Besides, MXSG might play an inflammation and immune regulatory role to prevent cytokine storm, relieve lung injury through TLRs signaling pathway. In addition, the above regulatory pathways of MXSG were further validated through transcriptome of the LPS-induced pneumonia model. In summary, MXSG is a relatively effective and safe treatment for influenza and viral pneumonia, and its therapeutic effect may be attributed to its antiviral and anti-inflammatory effects.